Pediatric Invasive Pneumococcal Disease in the United States in the Era of Pneumococcal Conjugate Vaccines - Tan, Tina Q. (American Society for Microbiology, 2012)
Summary: Invasive infections caused by Streptococcus pneumoniae continue to be a major cause of morbidity and mortality worldwide, especially in children under 5 years of age. In the United States, 90% of invasive pneumococcal infections in children are caused by 13 serotypes of S. pneumoniae. The licensure (in 2000) and subsequent widespread use of a heptavalent pneumococcal conjugate vaccine (PCV7) have had a significant impact on decreasing the incidence of serious invasive pneumococcal disease (IPD) in all age groups, especially in children under 2 years of age. However, the emergence of replacement non-PCV7 serotypes, especially serotype 19A, has resulted in an increase in the incidence of serious and invasive infections. In 2010, a 13-valent PCV was licensed in the United States. However, the impact that this vaccine will have on IPD remains to be seen. The objectives of this review are to discuss the epidemiology of serious and invasive pneumococcal infections in the United States in the PCV era and to review some of the pneumococcal vaccines that are in development.